Review study of source retention of rainwater as a means of peak discharge reduction an urban environment - Ng, Jenny Beng Chin (2017)
The objective of this study is to propose water retention features to reduce the peak urban runoff at source during a storm event in an urbanised area. This report focuses on the applications of the features in a decentralised area with a centralised system where surplus or uncontrolled runoff from each sub-catchment area will come together at one point and discharge into public drains. The three main proposed features are water towers, rooftop garden (planter tanks) and permeable pavements are to be implemented in residential housings such as HDB public housings. The aim is to find out how much water can be delayed in an event of high rainfall. Computations and reasoning of the proposed features are then discussed in this report.